Implementasi Pelayanan Administrasi Kependudukan E- Ktp Bagi Disabilitas Di Kabupaten Manggarai Timur - Patu, Frederikus; Pramudiana, Ika Devy (Institut Riset dan Pengembangan Indonesia, 2023)
This research aims to examine the implementation of E-KTP Population Administration Services for People with Disabilities in East Manggarai Regency. by using theory according to George C. Edwards III, there are four variables in public policy, namely communication (Communications), Resources (Resources), attitudes (Dispositions or Attitudes). The method used is descriptive qualitative. Data collection techniques used in this research include observation, interviews and documentation. Based on the results of research using George C Edward III's theory at the East Manggarai Regency Population and Civil Registration Service, it can be said that communication has been running optimally because the Dukcapil have been effective and efficient in carrying out socialization. Based on the results of the interview analysis on June 22 to June 28 of 2023, for the Resource variable, it can be said that the implementation process is going well because the socialization material is there based on the results of interviews with the community, and for the disposition variable it can be said that it has gone well and well due to several factors, namely officers who work at the East Manggarai Regency Dukcapil providing services wholeheartedly and definitely serve the community well. This bureaucratic structure is quite good and works well because it consists of all the officers in the East Manggarai Regency Dukcapil, the SOP runs well and the officers also carry it out because the SOP is a guide for officers when working.